Successful Decision-making A Systematic Approach to Complex Problems - Grünig, Rudolf; Kühn, Richard (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Making decisions is certainly the most important task of a manager and it is often a very difficult one. This book offers a decision making procedure for solving complex problems step by step. Unlike other texts, the book focuses on problem analysis, on developing solution options and on establishing the decision making matrix. The book is intended for decision makers in companies, in non-profit organisations and in public administration. It is an approach to helping them to solve complex problems successfully. The book is also addressed to students and to participants in executive courses.